PROBLEM SOLVING LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN PADA MAHASISWA: PROBLEM SOLVING LITERASI KEUANGAN TERHADAP PERILAKU KEUANGAN PADA MAHASISWA - Windy Yesika Siagian; M. Chaerul Rizky (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
Every individual has different financial characteristics and behavior. This is caused by factors that influence them both internally and externally. Internal influences are influences from within themselves such as psychology, attitudes and character that influence a person's financial behavior. Everyone must be able to manage their finances so that they can wisely use money as best as possible according to their needs so that the person becomes more prosperous. However, not everyone can organize and manage their finances according to their income and living expenses. This can lead to bankruptcy because the person does not have good financial management behavior.. Keywords: Financial Literacy, Financial Behavior, Students